2004
DOI: 10.1111/j.1651-2227.2004.tb02715.x
|View full text |Cite
|
Sign up to set email alerts
|

Faecal elastase‐1 test is superior to faecal lipase test in the assessment of exocrine pancreatic function in cystic fibrosis

Abstract: Among indirect tests, faecal elastase-1 test is superior to faecal lipase test in the assessment of exocrine pancreatic function in cystic fibrosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 12 publications
1
37
0
2
Order By: Relevance
“…Chymotrypsin can be used to monitor enzyme substitution therapy as it reflects the amount of enzymes taken by the patient (fecal excretion will be low in patients who are not compliant). However, diagnostic accuracy of fecal chymotrypsin and of fecal lipase appears to be inferior to that of fecal elastase [71,72]. …”
Section: Cystic Fibrosis and Other Hereditary Diseasesmentioning
confidence: 80%
“…Chymotrypsin can be used to monitor enzyme substitution therapy as it reflects the amount of enzymes taken by the patient (fecal excretion will be low in patients who are not compliant). However, diagnostic accuracy of fecal chymotrypsin and of fecal lipase appears to be inferior to that of fecal elastase [71,72]. …”
Section: Cystic Fibrosis and Other Hereditary Diseasesmentioning
confidence: 80%
“…Fecal chymotrypsin is another indirect pancreatic function test, which has a lower sensitivity than E1 in CF patients [35]. Fecal lipase is not widely used, and it was shown that the diagnostic value of E1 is superior [36]. The classical Van de Kamer method of total stool fat content measurement is more cumbersome in application [15].…”
Section: Discussionmentioning
confidence: 99%
“…Se evaluaron el estado nutricional (valores estandarizados de talla y peso corporales, concentración de albúmina 23 ), la expresión clínica de la enfermedad (función pulmonar, espirometría, función pancreática exocrina, elastasa-1 fecal, [24][25][26] colonización por Pseudomonas aeruginosa y marcadores bioquímicos de daño hepático [ALT, AST, GGT, 27 TP 28 ]) al momento de la recolección de muestras de sangre en todos los pacientes. También se recabó información sobre diabetes y cirrosis hepática concurrentes.…”
Section: Población Y Métodosunclassified